Next-Generation Sequencing Revealed Disease-Causing Variants in Two Genes in a Patient With Combined Features of Spherocytosis and Antley-Bixler Syndrome With Genital Anomalies and Disordered Steroidogenesis - Song, Fuying; Feng, Shunqiao; Shen, Xiang; Du, Mu; Yin, Hui; Liu, Rong; Chen, Xiaobo (Frontiers in Genetics, 2020)
Conventionally, patients with combined rare diseases are often difficult to diagnose. This is because some clinicians tend to consider the multiple disease symptoms as the presentation of a complicated “syndrome.” This pattern of thinking also confines their way of filtering pathogenic mutations. Some real pathogenic mutations might be ignored due to not covering all disease presentations. Here we report the case of a girl who was suffering from spherocytosis and Antley-Bixler syndrome with genital anomalies and disordered steroidogenesis. She remained undiagnosed even after targeted gene detection before. However, after performing next-generation sequencing and analyzing the sequencing data, we identified two mutations: c.2978T > A in ANK1 and c.1370G > A in POR. Our findings and experiences in diagnosing these mutations could contribute to the existing knowledge on the clinical and genetic diagnosis of patients with disease presentations in multiple systems.